2017
DOI: 10.1111/phn.12367
|View full text |Cite
|
Sign up to set email alerts
|

Caries risk assessment tool and prevention protocol for public health nurses in mother and child health centers, Israel

Abstract: Objectives: Dental caries is the most prevalent chronic disease in children. Caries risk assessment tools enable the dentists, physicians, and nondental health care providers to assess the individual's risk. Intervention by nurses in primary care settings can contribute to the establishment of oral health habits and prevention of dental disease. In Israel, Mother and Child Health Centers provide free preventive services for pregnant women and children by public health nurses. Materials and Methods:A caries pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…cluster randomized controlled trial (28) ; 7-Identifying attitudes, beliefs and reported practices of nurses and doctors as immunization providers (29) ; 8-Theory of the response to the item in research in public health (30) ; 9-Public health nurses' activities at a time of specialization in nursing -a national study (31) ; 10-Caries risk assessment tool and prevention protocol for public health nurses in mother and child health centers, Israel (32) ; 11-Public Health Nurses in Israel: A Case Study on a Quality Improvement Project of Nurse's Work Life (33) ; 12-Public Health Nursing Activities: Visible or Invisible? (33) ; 13-Risk-Reduction Strategies to Expand Radon Care Planning with Vulnerable Groups (35) ; 14-A Systematic Method to Document…”
Section: Barriers and Facilitators In The Delivery Of Environmental Risk Reduction By Public Healthmentioning
confidence: 99%
“…cluster randomized controlled trial (28) ; 7-Identifying attitudes, beliefs and reported practices of nurses and doctors as immunization providers (29) ; 8-Theory of the response to the item in research in public health (30) ; 9-Public health nurses' activities at a time of specialization in nursing -a national study (31) ; 10-Caries risk assessment tool and prevention protocol for public health nurses in mother and child health centers, Israel (32) ; 11-Public Health Nurses in Israel: A Case Study on a Quality Improvement Project of Nurse's Work Life (33) ; 12-Public Health Nursing Activities: Visible or Invisible? (33) ; 13-Risk-Reduction Strategies to Expand Radon Care Planning with Vulnerable Groups (35) ; 14-A Systematic Method to Document…”
Section: Barriers and Facilitators In The Delivery Of Environmental Risk Reduction By Public Healthmentioning
confidence: 99%
“…The Ministry acts in the prevention arena, as well. Lately, prevention of dental disease has been extended to Mother and Child Health Centers [5], where public health nurses perform Caries Risk Assessment and apply the appropriate preventive measures. This initiative started a couple of years ago in the south of the country, and it is spreading gradually to other areas as well.…”
Section: Main Textmentioning
confidence: 99%
“…In the in-depth phone interviews, nurses stated that the integration of the program into their busy daily schedule was realistic and appropriate. The lack of a specific dental module for managing computerized data was mentioned as an implementation difficulty (13).…”
Section: Early Childhood Caries Prevention Programmesmentioning
confidence: 99%